THE CHARACTER DEVELOPMENT OF ISABELLA LINTON IN EMILY BRONTE’S WUTHERING HEIGHTS NOVEL - Marselina Mistin Asmiaty; Singgih Daru Kuncara; Indah Sari Lubis (Fakultas Ilmu Budaya Universitas Mulawarman, 2022)
The purposes of this research were to find the character development of Isabella Linton and what are the events that influence Isabella Linton’s character development. This research applied an objectives approach and the researcher used Emily Bronte's Wuthering Heights novel as the source of data. The data were taken from the dialogues between characters and narrations that indicate Isabella Linton’s character development based on Kenan’s theory and the events that influence Isabella Linton’s character development based on Griffith’s theory. The finding of this research using Kenan’s theory showed that Isabella Linton experienced character development from a spoiled and innocent young lady became a brave, responsible, and independent woman. Then, the finding using Griffith’s theory of plot showed that Isabella Linton experiences character development at the exposition events, rising action, climax, falling action, and stable situation.